2019
DOI: 10.1002/14651858.cd005343.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy versus surgery for initial treatment in advanced ovarian epithelial cancer

Abstract: Background Epithelial ovarian cancer presents at an advanced stage in the majority of women. These women require surgery and chemotherapy for optimal treatment. Conventional treatment is to perform surgery first and then give chemotherapy. However, it is not yet clear whether there are any advantages to using chemotherapy before surgery. Objectives To assess whether there is an advantage to treating women with advanced epithelial ovarian cancer with chemotherapy before cytoreductive surgery (neoadjuvant chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 145 publications
0
39
0
Order By: Relevance
“…Although some of them have been already recommended by updated NCCN guidelines for ETOC and PPSC treatment [4,26], they are not widely used in the routine clinical practice [60]. Among these, induction chemotherapy (neoadjuvant chemotherapy-NACT) using either standard form of paclitaxel and carboplatin or its modification form, including dose-dense or high-dose chemotherapy, and in additional adding bevacizumab, has become more and more popular, especially for those patients who are not candidates for immediate PCS [61][62][63][64][65][66][67][68][69].…”
Section: Current Standard Of Treatmentmentioning
confidence: 99%
“…Although some of them have been already recommended by updated NCCN guidelines for ETOC and PPSC treatment [4,26], they are not widely used in the routine clinical practice [60]. Among these, induction chemotherapy (neoadjuvant chemotherapy-NACT) using either standard form of paclitaxel and carboplatin or its modification form, including dose-dense or high-dose chemotherapy, and in additional adding bevacizumab, has become more and more popular, especially for those patients who are not candidates for immediate PCS [61][62][63][64][65][66][67][68][69].…”
Section: Current Standard Of Treatmentmentioning
confidence: 99%
“…Most of these comprise of advanced ovarian cancers and neoadjuvant treatment is non inferior to extensive cytoreductive surgery. [27] There is a clause on performing extensive cytoreductive surgery (CRS) during the pandemic as intensive care beds need to be reserved preferably for COVID patients. Reduced blood donation camps leading to shortage of blood products also is a limiting factor for performing CRS with or without HIPEC.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, primary debulking surgery (PDS) was better in OS and DFS than interval debulking surgery (IDS) for FIGO stage III epithelial ovarian carcinoma. In most of the previous studies, there is no consensus regarding this point which may be due to combining both FIGO stage III and IV as advanced ovarian cancer as well as the differences in the design of the studies [13]- [18]. Therefore, in our study, we evaluated FIGO stage III epithelial ovarian carcinoma separately that may explain more details about the outcome of this category of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bristow and Chi published a meta-analysis that involved more than 800 patients, showed that NACT compared with PDS was associated with a worse OS, and they suggested that the definitive operative intervention should be performed as early in the treatment program as possible [12]. However, a more recent meta-analysis of multiple central randomized trials concluded that survival was similar in patients treated with NACT followed by interval debulking surgery compared to primary debulking followed by chemotherapy, and they even criticized Bristow and Chi meta-analysis [13] [14]. Therefore, the aim of this retrospective study is to evaluate the outcome of IDS after primary NACT compared to PDS followed by adjuvant chemotherapy for FIGO stage III epithelial ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%